Analysis Suppliers Selection of the Construction Raw Material in PT. Y Using VIKOR Method - Octavia Olga Citra Dewi; Erma Suryani (Institut Teknologi Sepuluh Nopember, 2019)
Improving supply chain management is one way to excel in competition. The selection of suppliers is an important part because the lack of proper supplier selection can lead to losses for the company. In its practice, the supplier selection process is more frequently based on a supplier that can provide the lowest price. This happens because the supplier selection process is considered to be at the operational level and not at the strategic level. The number of raw material suppliers on the construction project makes the developers be careful in choosing the material that is according to the developers’ plans. All this time, the selection of suppliers involves many factors, sometimes a supplier has a good performance in terms of the delivery process, yet lacks in terms of quality compared to other suppliers and vice versa. Therefore, research must be done with a method that can take the factors, both the qualitative and quantitative, into consideration. This study is conducted to identify the factors of the selection of construction raw material suppliers and the support of alternative decision support in the selection of construction raw material suppliers. The purpose of this research is to identify the factors of the selection of raw material suppliers and the support of alternative decision in the selection of construction raw material suppliers. This research is expected to help the construction industry, especially in the city of Jember regarding the importance of knowing the factors of the selection of construction raw material suppliers and the decision of the selection of construction raw material suppliers especially if the selection of the construction raw material is in the power of the developer. The method used is the integration of AHP and Vikor using rough number. This research is expected to facilitate the process of selecting raw material suppliers and the selection of its alternatives.The results of this study gain the order of priority of 9 criteria and 23 sub-criteria. The recommended selection of suppliers based on its ranking on the sand suppliers is sand supplier P3, sand supplier P2, and sand supplier P1. Meanwhile, the ranking for the coral suppliers is coral supplier K3, then coral supplier K2, and lastly coral supplier K1